cis-acting genomic elements and trans-acting proteins involved in the assembly of RNA viruses - Schlesinger, Sondra (Semin. Virol, 1994)
There is now considerable evidence that a specific site (or sites) in the genome of an RNA virus interacts with a viral protein to initiate the assembly of the virus ribonucleoprotein or nucleocapsid. We describe the progress that has been made in defining these elements for a number of different viruses: the togavirus, Sindbis virus; the coronavirus, mouse hepatitis virus; influenza A virus; several retroviruses; and the hepadnavirus, hepatitis B virus. The importance of cis-acting elements in packaging has been established for all of these viruses. For Sindbis virus, specificity in the binding of the RNA element to a region of the viral capsid protein in vitro has also been demonstrated.